Implementasi Metode Linear Discriminant Analysis (LDA) Pada Klasifikasi Tingkat Kematangan Buah Nanas - Destriana, Rachmat; Nurnaningsih, Desi; Alamsyah, Dedy; Sinlae, Alfry Aristo Jansen (Building of Informatics, Technology and Science (BITS), 2021)
Pineapple is a fruit commodity that is Indonesia's flagship. This is because pineapple is a fruit that has the highest export volume in Indonesia. To obtain pineapples with perfect ripeness, generally manually selected, this becomes inefficient if large numbers of pineapples are selected. So, in this study, an image processing system will be developed that can classify pineapple ripeness based on its image. In this study, the color feature extraction used is feature extraction based on hue and saturation values. Color feature extraction with hue and saturation is used to obtain various information from the colors in the image so as to facilitate the identification process. Furthermore, Linear Discriminator Analysis will obtain optimal projections to be able to enter spaces with smaller dimensions by performing pattern recognition that can be separated so that they can be grouped based on boundary lines obtained from linear equations. Based on the results of the accuracy test, the accuracy rate reaches 83%, it is in the good category